Pelatihan Cara Pintar Mengatur Keuangan Keluarga Berpendapatan Rendah - Djulius, Horas; Rostiana, Endang (Jurnal Pengabdian Pada Masyarakat, 2022)
Managing family finances is unquestionably critical, even more so for low-income families. The issue is that many low-income families are characterized by family heads who are either uneducated or lack basic skills of family finance management. The goal of the activities is to ascertain the beneficiary community’s need for financial management, to provide training in managing family finances to low-income families, and to evaluate the training. The targeted communities are people with a low to moderate income who live in the Padalarang-West Java region. Three techniques are utilized depending on the number of activity objectives. The first objective is accomplished by in-depth interviews with community leaders, the second objective is accomplished through training, and the third objective is accomplished through questionnaire analysis. The study’s findings indicated that the community required an understanding of and capacity for managing family finances, particularly during a pandemic. This comprehension and capability were acquired through the training provided, which, according to participants, was highly effective.